Antibacterial Activity of Leaf Extracts from Azadirachta indica A. juss and Solanum trilobatum Linn - SANTHI*, P.R.; POONGOTHAI†, G. (Asian Journal of Chemistry, 2024)
In this study, the antimicrobial activity of Azadirachta indica A.juss and Solanum trilobatum Linn plants leaves were taken for the study.The green leaves of the Azadirachta indica A. juss and Solanumtrilobatum Linn plants, was extracted by aqueous method in aspeticalmanner. Whatman filter paper No.1, discs were used impregnation inthe aqueous solution Azadirachta indica A. juss and Solanum trilobatumLinn extract and dried at 37 ºC and sterilized in air oven at 80 ºC for2 h. The medicinal efficacy was examined against Escherichia coli andKlebsiella pneumoniae by observing the sensitive zone to the herbalextract discs.